Peningkatan Perilaku Aman di PT. XXX dengan Pendekatan Behavior Based Safety - Chintia Mokaliran; Togar W.S Panjaitan (Jurnal Titra, 2015)
PT. XXX has applied Health Safety Enviroment system, but still experienced relatively high level of accidents. The accident number was up to 11 out of a total worker of 390 in 2014. PT XXX would like to decrease to zero accident so as the production process runs smoothly.The method used in this problem was Behavior Based Safety. BBS method provides training for the worker to behave safely. This method gave good results in that all processes had an average of 80% safety behavior. BBS changed many dangerous behavior to become safety behavior, but there is still a dangerous behavior that cannot be changed.